Design and Simulation of Linear Array Antenna Using Koch Dipole Fractal Antenna Elements for Communication Systems Applications - Fawwaz Jinan Jibrael; Mohanad Ahmed Abdulkareem (Engineering and Technology Journal, 2010)
In this paper, the fractal concept has been used in the linear array antennadesign to obtain multiband operation. The fractal linear array antenna has beendesigned at a frequency of 750 MHz with equal spacing and uniform amplitudedistribution of the elements array. 1st iteration quadratic Koch curve dipole fractalelement is used in design of the array. The proposed antenna array design, analysisand characterization had been performed using the Method of Moment (MoM)technique. The radiation pattern, side lobe level (SLL), directivity (D), and inputimpedance of the proposed antenna are described and simulated using 4NEC2software package and MATLAB programming language version 7.6.